Chemodiversity and Antioxidant Potential of the Essential Oil of Fresh Leaves of Cinnamomum zeylanicum Blume from Uttarakhand. Issue 4 (4th July 2022) - Rani, Akanksha; Kanyal, Bhawana; Aabha,; Tewari, Geeta; Pande, Chitra; Prakash, Om
Abstract: Cinnamomum leaves are used extensively as spices in food and to produce essential oils for flavoring and preservation of food besides having a number of biologically active compounds making it an important part of our traditional systems of medicines. The leaves of Cinnamomum zeylanicum were collected from three different attitudes of Uttarakhand to examine the chemical profile and antioxidant potential of their essential oil. The GC/GC/MS analysis of the oils resulted in the identification of total 15, 26 and 17 compounds from Mangoli, Ramnagar and Pantnagar representing 97.1%, 93.2%, 92.6%, of the oil respectively. The effect of different altitudes on the composition of essential oil was remarkable. ( E )-Cinnamaldehyde being the highest in the Ramnagar (67.5%), ( E ) - cinnamyl acetate in Mangoli (39.9%) and linalool in Pantnagar (31.4%) collection. The oil samples were found to be rich in phenyl propanoids (90.8% in Mangoli, 76.5% in Ramnagar, 36.8% in Pantnagar). Sesquiterpenes were found to be the minor constituents. The essential oil yield and IC50 values correlated positively with the altitude.